2022
DOI: 10.2147/ndt.s371483
|View full text |Cite
|
Sign up to set email alerts
|

Rett Syndrome and MECP2 Duplication Syndrome: Disorders of MeCP2 Dosage

Abstract: Rett syndrome (RTT) is a neurodevelopmental disorder caused predominantly by loss-of-function mutations in the gene Methyl-CpG-binding protein 2 ( MECP2 ), which encodes the MeCP2 protein. RTT is a MECP2 -related disorder, along with MECP2 duplication syndrome (MDS), caused by gain-of-function duplications of MECP2 . Nearly two decades of research have advanced our knowledge of MeCP2 function in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 223 publications
0
20
0
2
Order By: Relevance
“…Accordingly, missense variations such as R106W, T158M, p.Thr158Ala (T158A) and p.Tyr120Asp (Y120D) express reduced protein levels compared to the wild-type product ( Goffin et al, 2012 ; Johnson et al, 2017 ; Lamonica et al, 2017 ; Gandaglia et al, 2019 ). Interestingly, among nonsense mutations, the R294X produced stable truncated proteins whereas the R168X, R255X, and R270X did not yield to a detectable product ( Collins and Neul, 2022 ). It is subject of debate whether global MeCP2 deficiency correctly recapitulates the molecular features of the disease.…”
Section: Mouse Models Of Mecp2 -Related Disordersmentioning
confidence: 99%
“…Accordingly, missense variations such as R106W, T158M, p.Thr158Ala (T158A) and p.Tyr120Asp (Y120D) express reduced protein levels compared to the wild-type product ( Goffin et al, 2012 ; Johnson et al, 2017 ; Lamonica et al, 2017 ; Gandaglia et al, 2019 ). Interestingly, among nonsense mutations, the R294X produced stable truncated proteins whereas the R168X, R255X, and R270X did not yield to a detectable product ( Collins and Neul, 2022 ). It is subject of debate whether global MeCP2 deficiency correctly recapitulates the molecular features of the disease.…”
Section: Mouse Models Of Mecp2 -Related Disordersmentioning
confidence: 99%
“…There is extensive literature on the use of mouse models in RTT and MDS [61]. Previous work has shown that even mild overexpression of MeCP2 can lead to progressive neurological deterioration in mice [62].…”
Section: Other Considerationsmentioning
confidence: 99%
“…Gene dosage disorders, in which either too much or too little of a gene cause disease, are strongly linked to psychiatric, cognitive, and behavioral impairments (Genovese & Butler, 2023; Levitis et al, 2024; Morris, 2023; Vicari, 2006). One well‐studied example of gene dosage disorders are diseases caused by the X‐linked MECP2 (methyl CpG‐binding protein‐2) gene, a transcriptional regulator of thousands of genes (Collins & Neul, 2022). MECP2 is associated with two major neurodevelopmental disorders: Rett syndrome (RTT) and MECP2 duplication syndrome (MDS) (Sandweiss et al, 2020).…”
Section: Introductionmentioning
confidence: 99%